Acupuncture for postoperative delirium (POD): A systematic review and meta-analysis protocol. Issue 3 (22nd January 2021) - Joo, Chanwoo; Lee, Seunghoon; Kang, Jung Won; Lee, Jae-Dong
Abstract: Background: Postoperative delirium (POD) is a form of delirium that is newly diagnosed after a surgical procedure. This study aims to examine the effectiveness and safety of acupuncture treatment for POD in patients who underwent surgery. Methods: Randomized controlled trials for patients diagnosed with POD using validated delirium assessment scales will be included in this review. Electronic databases, such as MEDLINE, EMBASE, CENTRAL, CINAHL (English DB), CNKI, Wanfang, VIP (Chinese database), KoreaMed, RISS, KISS, DBpia, OASIS (Korean DB), and J-STAGE (Japanese DB) will be searched without language limitation from their inception to October 2020. The intervention group will include patients who have received any type of acupuncture treatment for POD. The control group will include individuals with no treatment, sham acupuncture treatment, and conventional treatment. The primary outcome is the incidence of POD in each study. Quality assessment will be performed using the Cochrane risk of bias tool. A meta-analysis will be performed to pool the estimated effect. Conclusion: This study will provide evidence for acupuncture as a potential treatment for POD, in researchers, patients, and policy makers. Dissemination: The result of the study will be disseminated through posters, press releases, conference presentations, and peer-reviewed papers. Trial registration number: OSF 2020: (https://osf.io/usvdg )